Comparison of the reflex reactivity of skin and muscle veins in the human forearm - Zelis, Robert; Mason, Dean T. (The Journal of clinical investigation, 1969)
To determine the relative participation of skin and muscle capacitance beds of the forearm in venomotor reflexes, epinephrine iontophoresis was combined with forearm plethysmography so that the volume of muscle veins could be estimated simultaneously with the volume of cutaneous veins, at a constant venous pressure. With this technique not only are the cutaneous veins markedly constricted but they also are prevented from filling since skin blood flow is abolished. In 10 normal subjects, the venous volume in the elevated control forearm at a congesting pressure of 30 mm Hg (VV[30]) was 3.16 +/-0.30 SEM cc/100 cc, while in the iontophoresed arm it was 2.54 +/-0.31 cc/100 cc. Thus the forearm cutaneous VV[30] was 1.62 cc/100 cc. With a deep breath, ice to the forehead, and leg exercise, and cutaneous VV[30] decreased 19.8% (P < 0.01), 36.6% (P < 0.01), and 32.6% (P < 0.02), respectively, whereas the muscle VV[30] was not altered significantly. Similar results were observed using the isolated forearm technique and a deep muscle vein. The infusion of epinephrine intra-arterially did not decrease reflex venomotor reactivity until cutaneous blood flow was completely suppressed, indicating that the inability of the veins to react in the iontophoresed arm was not the result of epinephrine diffusion into the muscle bed. Thus, these results indicate that, in the forearm, only cutaneous veins participate in venomotor reflexes. Further, since the forearm is principally composed of skeletal muscle and the hand skin, an explanation is provided for the observation that veins of the forearm, studied as a whole, appear less reactive to stimuli than veins of the hand. An explanation also is provided for fainting which occurs during motionless standing despite intense venoconstriction, thereby emphasizing the importance of the skeletal muscle pump in the legs in preventing postural syncope.